Fetal Cerebrovascular Response to Maternal Hyperoxia Testing and Association With Brain Growth and Postnatal Brain Injury in Congenital Heart Disease - Taleb, Mariam; Liu, Jing; Xu, Duan; Zhao, Yii; Moon‐Grady, Anita J.; McQuillen, Patrick S.; Peyvandi, Shabnam (Journal of the American Heart Association, 2025)
Neurodevelopmental outcomes are impaired in significant congenital heart disease (CHD) with prenatal origins. The cerebrovascular response to maternal hyperoxia (MH) varies in fetuses with CHD, which may reflect brain health in utero. We investigated the association between lack of cerebrovascular reactivity with MH and adverse neurologic outcomes in CHD measured as brain growth and risk of postnatal white matter injury. This is a prospective cohort study of pregnant participants whose fetuses had CHD requiring a neonatal operation. We performed fetal echocardiograms with MH, fetal brain magnetic resonance imaging (MRI), and postnatal preoperative brain MRI. A ≥5% change in middle cerebral artery pulsatility index with MH defined reactivity. Total brain volume was measured on MRIs. The neonatal MRI was assessed for white matter injury. Regression analyses compared responders versus nonresponders, then stratified by hypoplastic left heart syndrome and d-transposition of the great arteries groups. Fifty-five participants underwent fetal imaging. Forty-nine neonates underwent brain MRI. Among subjects with hypoplastic left heart syndrome, at each gestational week, total brain volume was 17.8 mL greater in responders (95% CI, 3.3-32.3; =0.02). This pattern was not seen in d-transposition of the great arteries. Postnatal white matter injury was less common in responders. Lack of fetal cerebrovascular response to MH is associated with smaller total brain volume beginning in utero in hypoplastic left heart syndrome. Postnatal white matter injury is more common among nonresponders. MH testing can help identify individual fetuses with CHD at highest risk for adverse neurologic outcomes, particularly those with hypoplastic left heart syndrome.